1995
DOI: 10.1136/sti.71.6.358
|View full text |Cite
|
Sign up to set email alerts
|

AIDS in Africans living in London.

Abstract: either the AIDS-defining diagnosis or was detected within three months of this event. Sixty-two per cent of TB cases were diagnosed within twelve months of entry to the UK compared to 34% of all other AIDS cases. The prevalence of STD was very low; genital herpes was the commonest STD: 17% of the women, 9% men; 28% of the men and 11% of the women tested had a positive TPHA test. In cases known to be HIV-positive prior to an AIDS diagnosis, 41% took prophylaxis for PCP and 45% had taken zidovudine (ZDV). Forty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…In contrast to London, where the unmet needs of Africans became evident in the 1990s (Low et al, 1995;O'Farrell et al, 1995;Del Amo et al, 1996;McMunn et al, 1997;Erwin & Peters, 1999), HIV service providers and public health personnel in American cities have only recently become aware of this new patient group. The findings presented here confirm the conclusions of the Nasah study, which suggest that health interventions must focus on income-generation and other basic needs, and improving access to health information for African immigrants (Weatherburn et al, 2003).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast to London, where the unmet needs of Africans became evident in the 1990s (Low et al, 1995;O'Farrell et al, 1995;Del Amo et al, 1996;McMunn et al, 1997;Erwin & Peters, 1999), HIV service providers and public health personnel in American cities have only recently become aware of this new patient group. The findings presented here confirm the conclusions of the Nasah study, which suggest that health interventions must focus on income-generation and other basic needs, and improving access to health information for African immigrants (Weatherburn et al, 2003).…”
Section: Resultsmentioning
confidence: 84%
“…African immigrants in the US represent a small portion of the HIV-affected population, but they may exhibit patterns similar to Africans living in London, such as having low selfperceived risk of HIV/AIDS (Erwin et al, 2002;Fenton et al, 2002) being diagnosed later than Americans (O'Farrell et al, 1995;Low et al, 1996) being slower to accept antiretroviral treatment (Del Amo et al, 1996), and having less knowledge of HIV treatment than Americans (Weatherburn et al, 2003). One study of Africans in London living with HIV reported social anxiety about disclosing their status and a high degree of mistrust of medical personnel (Erwin & Peters, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Although late diagnosis may be related to ethnicity6 9 we did not find evidence that uptake of medical interventions after diagnosis was significantly associated with presumed mode of acquisition of the virus or ethnicity.…”
contrasting
confidence: 39%
“…The majority of heterosexually acquired HIV infections in Europe are now in immigrants from high prevalence countries, who, like persons from ethnic minorities, present late to health services [116][117][118]. For example, in the UK, black Africans with HIV/AIDS, were more likely to present to outpatient clinics at an advanced stage of disease, but once diagnosed with HIV, their use of services was similar to that of the PLWHA who were not of black African origin [119][120][121][122][123][124][125]. Similarly, Italian IDUs in the UK experienced difficulties in accessing services [126].…”
Section: Services For the Socio-economically Disadvantaged Groupsmentioning
confidence: 98%